2018
DOI: 10.1002/jat.3726
|View full text |Cite
|
Sign up to set email alerts
|

The toll like receptor 4‐myeloid differentiation factor 88 pathway is essential for particulate matter‐induced activation of CD4‐positive cells

Abstract: Asian sand dust (ASD), a type of particulate matter (PM) found in Asia, can be transported to East Asia. We recently found that acute splenic inflammation is induced by ASD in mouse models. In this study, we examined the effect of sub‐chronic ASD exposure on mouse immune cells. Mice were intratracheally administered ASD once every 2 weeks for 8 weeks and killed 24 hours after the final administration. Wild‐type (WT) mice showed increased cell viability after ASD administration. In contrast, ASD administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…Despite the wealth of animal studies investigating the way in which ASD induces pulmonary inflammation, a limited understanding exists regarding the inflammatory effects of ASD on other organs. Since immune cells residing in peripheral lymphoid organs and circulating to sites of inflammation play important roles in allergy, the effects of AASD on splenic events have been investigated ( Song et al, 2015 , Song et al, 2019 ). Song et al (2015) showed that administration of AASD (IT 100 μg; heat treated and untreated), collected from the atmosphere at Kitakyushu in Japan, to ICR mice induced pulmonary inflammation (increased TNF-α in BALF) on day 1 but not day 3, and modified peripheral lymphoid splenocytes on day 3 but not day 1, suggesting a triggering of systemic inflammation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the wealth of animal studies investigating the way in which ASD induces pulmonary inflammation, a limited understanding exists regarding the inflammatory effects of ASD on other organs. Since immune cells residing in peripheral lymphoid organs and circulating to sites of inflammation play important roles in allergy, the effects of AASD on splenic events have been investigated ( Song et al, 2015 , Song et al, 2019 ). Song et al (2015) showed that administration of AASD (IT 100 μg; heat treated and untreated), collected from the atmosphere at Kitakyushu in Japan, to ICR mice induced pulmonary inflammation (increased TNF-α in BALF) on day 1 but not day 3, and modified peripheral lymphoid splenocytes on day 3 but not day 1, suggesting a triggering of systemic inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Effects on splenocytes were an increased mitogen-induced IL-2, TNF-α and IL-6 production as well as enhanced activation of NF-κB in CD4 + and CD11b + cells. These researchers went on to study effects of a subchronic exposure to AASD by administering mice with AASD once every 2 weeks for 8 weeks ( Song et al 2019 ). The results of an elegant series of experiments using wild-type and knockout (TLR2 −/− , TLR4 −/− and MyD88 −/− ) mice indicate that the AASD particle (as opposed to particle constituents) induced splenic inflammation via TLR4-MyD88 signaling.…”
Section: Resultsmentioning
confidence: 99%
“…The upregulated expression levels of IL-1β, IL-6, IL-12, IL-17A, KC, MCP-1 and TNF-α may contribute to airway neutrophilia and asthma exacerbation [34–40]. The enhancement of H-ASD on LPS-induced inflammation may react through TLR4/MyD88-dependent pathway, given that the results of a recent study indicate that H-ASD-induced NF-κB activation affects the expression levels of inflammatory proteins through TLR4/MyD88-dependent pathway [41]. Besides, the LPS-induced overexpression of these cytokines and chemokines may be primarily mediated by MAPKs and NF-κB kinases following TLR4 activation [26], and the LPS-induced MAPKs activation can also be regulated, at least in part, by reactive oxygen species (ROS) [42].…”
Section: Discussionmentioning
confidence: 99%
“…Production of ROS by SPM and formation of oxidative stress induce transmission of NF-κB and MAPK signals. Although both signaling pathways are activated upon exposure to SPM, the NF-κB pathway has been found to play a crucial role [57,[59][60][61][62]. Active oxygen species can directly affect cellular calcium channels, thereby disrupting the transmission of intracellular ionic signals.…”
Section: The Role Of Oxidative Stress Induced By Spm In the Formation...mentioning
confidence: 99%
“…Lung oxidant/antioxidant imbalance also leads to NF-κB activation [62]. SPM induces nuclear translocation of NF-κB and production of inflammatory cytokines in human bronchial epithelial cells [61,64].…”
Section: The Role Of Oxidative Stress Induced By Spm In the Formation...mentioning
confidence: 99%